Нова знахідка гриба Colletotrichum lupini (Bondar) Damm, P.F. Cannon & Crous з України - Фещенко, Н.А.; Feshchenko N.A. (Івано-Франківськ : Супрун В.П., 2023)
The second record of a phytopathogenic fungus Colletotrichum lupini from the territory of Ukraine is reported. It was collected on the dead overwintered stems of Lupinus polyphyllus Lindl. in the Zolochiv district of the Kharkiv region in the spring of 2023
New record of the fungus Colletotrichum lupini (Bondar) Damm, P.F. Cannon & Crous from Ukraine
Keywords: гриби; біорізноманіття; Харківська область; Україна